Cluster Introduction: Life Writing in Times of Crisis - Teresa Bruś; Paweł Rodak (European Journal of Life Writing)
We are pleased to present a special cluster of articles inspired by the IABA conference held in Warsaw from July 5–8, 2023, at the University of Warsaw. The conference, titled Life-Writing in Times of Crisis, also lends its name to this collection. During the conference, numerous thought-provoking presentations explored how experiences of crisis are documented in autobiographical literature. Contemporary crises can unfold on a collective scale — encompassing war, genocide, pandemics, or economic hardships such as inflation, unemployment, and housing instability — or on an individual level, involving illness, bereavement, imprisonment, forced confinement, hunger, homelessness, or involuntary displacement. These are all circumstances of unwanted change, sudden rupture, and discontinuity that often give rise to a sense of living in an unfamiliar, radically altered world. In such moments, various forms of life-writing emerge — diaries, memoirs, letters — many of which are represented in this cluster.